Maximum age for a concretion at Green Creek, Ontario - Gadd, Nelson (Géographie physique et Quaternaire, 1980)
Wood (? Salix sp.) from a concretionary nodule found at - 43 m a.s.l. at the Green Creek, Ontario, site was dated at 9 960 ± 820 BP (GSC-2498). The carbonate concretion has an apparent age of 14 400 ± 250 BP (GSC-2530). The wood date is a maximum age for the enclosing sediment and for its cementation; the carbonate date appears anomalous. At the time of the upper limit of error for the wood date (10 780 BP) Champlain Sea stood at or above 100 m a.s.l. The true age of the wood probably is compatible with that of freswhater shells at - 53 m a.s.l. at Bourget, Ontario (10 200 ± 90; GSC-1968), and of wood at - 61 m a.s.l. at Hawkesbury, Ontario (9 860 ± 330; BGS-257). Terrace sediments at ~ 43 m a.s.l. probably are of freshwater origin. Terrestrial and freshwater flora and fauna in earlier collections of concretions from Green Creek also suggest an estuarine to freswhater environment for the enclosing sediments. Occurrence of complete skeletons of fish and other vertebrates in concretions is related to chemically induced carbonate cementation during early stages of putrefaction of soft-bodied animals. This could preserve skeletal remains through several cycles of erosion. Therefore some concretions carry fossil remains that may be allochtonous to the sediment in which they now occur.